MSCs inhibit tumor progression and enhance radiosensitivity of breast cancer cells by down-regulating Stat3 signaling pathway. Issue 10 (October 2018) - He, Ningning; Kong, Yangyang; Lei, Xudan; Liu, Yang; Wang, Jinhan; Xu, Chang; Wang, Yan; Du, Liqing; Ji, Kaihua; wang, Qin; Li, Zongjin; Liu, Qiang
Abstract The acquisition of radioresistance by breast cancer cells during radiotherapy may lead to cancer recurrence and poor survival. Signal transducer and activator of transcription 3 (Stat3) is activated in breast cancer cells and, therefore, may be an effective target for overcoming therapeutic resistance. Mesenchymal stem cells (MSCs) have been investigated for use in cancer treatment. Here, we investigated the potential of MSC conditioned medium (MSC-CM) in sensitizing breast cancer to radiotherapy. It was found that MSC-CM could inhibit the level of activated Stat3, suppress cancer growth, and exhibit synergetic effects with radiation treatment in vitro and in vivo. Furthermore, MSC-CM reduced the ALDH-positive cancer stem cells (CSCs) population, modulated several potential stem cell markers, and decreased tumor migration, as well as metastasis. These results demonstrate that MSC-CM suppresses breast cancer cells growth and sensitizes cancer cells to radiotherapy through inhibition of the Stat3 signaling pathway, thus, providing a novel strategy for breast cancer therapy by overcoming radioresistance.